Understanding and addressing the treatment gap in mental healthcare: economic perspectives and evidence from China - Qin, Xuezheng; Hsieh, Chee-Ruey (SAGE Publications Inc., 2021)
A common challenge faced by the healthcare systems in many low- and middle-income countries is the substantial unmet mental healthcare needs, or the large gap between the need for and the provision of mental healthcare treatment. This paper investigates the potential causes of this treatment gap from the perspective of economics. Specifically, we hypothesize that people with mental illness face 4 major hurdles in obtaining appropriate healthcare, namely the high nonmonetary cost due to stigma, the high out-of-pocket payment due to insufficient public funds devoted to mental health, the high time costs due to low mental healthcare resource availability, and the low treatment benefit due to slow technology diffusion. We use China as a study setting to show country-specific evidence. Our analysis supports the above theoretical argument on the 4 barriers to access, which in turn sheds light on the effective approaches to mitigate the treatment gap. Four policy options are then discussed, including an information campaign for mental health awareness, increasing public investment in primary mental healthcare resources, transforming the healthcare system towards an integrated people-centered system and capitalizing on e-health technologies.